Toxicity Of volatile organic compounds (VOCs) mixtures using human derived cells - Khalil, C. (2010)
Assessing the effects of contaminants is an issue of high priority for governmental safety health and environmental agencies around the world. The general conservative consensus is that chemicals in mixtures interact by concentration addition. However, previous studies also report that concentration addition of mixture components does not always reflect the overall toxicity of a mixture. Volatile organic compounds (VOCs) such as Benzene, Toluene, Xylene and Formaldehyde (BTXF) belong to the air pollutants found in urban and indoor environments. They could trigger acute and chronic adverse health effects like allergy, respiratory and cardiovascular diseases. The volatile nature of these compounds poses additional problems in assessing individual volatile chemical toxicity let alone mixtures of these chemicals. Our research aims at establishing the true toxic effects of VOC exposure in vitro using a static direct exposure glass-chamber method. This was achieved by assessing and comparing individual and interactive effects of VOCs in exposed human epithelial lung (A549) and liver cells (HepG2) using the MTS cytotoxicity assay to assess cell viability upon VOC insult. The study results clearly indicated the limitation of the concentration addition method used in assessing volatile mixtures cytotoxicity and the need to develop new techniques for rapid and accurate mixture toxicity determination. The study may have implications for regulatory risk assessment of environmental volatile organic chemicals. Keywords: static method, MTS, cytotoxicity, lung cells, liver cells, VOCs. 1 Introduction Human environmental chemical exposures are characterised by exposures to direct multiple chemical combinations or sequential exposure to individual.